Corporate failure prediction : empirical evidence form the Kuala Lumpur stock exchange 2009-2013 - Teoh, Tsui Ven (Universiti Malaysia Sarawak (UNIMAS), 2015)
The objective of this study is to predict the corporate failure by using Altman Z-Scores Models. There are total of 30 public listed companies which are come from different kind of sectors are selected from Bursa Malaysia as sample and the period is collecting from 2009 until 2013. Altman Z-Score Models categorized the companies into three zones which are safe, grey and distress zone according to the z-score index of each company. This study collects secondary data from financial statements (income statement and balance sheet). Methodology such as descriptive statistics and correlation analysis have been done to analysis the relationship between variables. The findings of this study show that there is 8 out of 10 PN17 companies, which is 80% in distress zone, only one company in grey zone and distress zone, which carry 10% respectively. For 20 non PN17 companies, 12 companies out of them, which is 60% in safe zone, 3 companies in grey zone and 5 companies in distress zone which carry 15% and 25% accordingly.